Chanter son/l’homosexualité pour mieux l’affirmer : Suzane, Eddy de Pretto et autres échos dans la chanson française contemporaine - Renaud Lagabrielle (Transposition)
Suzane and Eddy de Pretto are two French singer-songwriters whose music encourages a direct and rare criticism of heterosexism. Fuelled by the principle of agency, their songs advocate for coming out as well as coming in, and celebrate gay longing and pleasure. This article examines the work and discourse of these two artists, whose common advocacy for LGBTQI+ rights can be observed in songs as well as in media interventions.